High-temperature corrosion of helium ion-irradiated Ni-based alloy in fluoride molten salt. (February 2015) - Zhu, Hanliang; Holmes, Rohan; Hanley, Tracey; Davis, Joel; Short, Ken; Edwards, Lyndon
Abstract: A comparison of the effect of helium-ion-radiation damage on a Ni–Mo–Cr–Fe alloy exposed to high-temperature (750 °C) corrosion in eutectic LiF–NaF–KF molten salt has been made. Microstructural examination showed that both the corroded-only and irradiated and corroded samples exhibit the characteristics of intergranular corrosion. However, helium ion irradiation introduces defects such as helium bubbles and cavities into the microstructure, greatly increasing intragranular corrosion of the irradiated sample. The thickness of the remaining corrosion zone for the irradiated sample was much greater than that for the unirradiated sample.